Classroom management and use of instructional aids (2004)
Classroom management, preparation and handling of instructional materials are crucial issues in present day teaching and learning. CIass room management in this context is the act or skill in the organization and presentation of lessons in such a way that all learners are actively involved in learning. Effective classroom management is not only positively related to certain attributes of the teacher, but it is also positively linked to the quality of the school environment and the nature of decision making process adopted by the school authority. As regards instructional materials and their preparation and use, this paper highlights their importance as instructional aids, especially the use of the computer in education. The present paper further discusses the various ways in which teaching aids could be obtained.